PENGARUH PELAKSANAAN TEKNIK BIRTH BALL TERHADAP KEMAJUAN PERSALINAN - Wilda Wahyuni Siregar; Supran Hidayat Sihotang; Sri Maharani; Julia Rohana (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2020)
Survey Demografi Kesehatan Indonesia (SDKI) year 2014 noted that 42.96% of prolonged labor was the main cause of maternal and perinatal death followed by bleeding 35.26% and eclampsia 16.44. Other efforts to prevent prolonged labor are the use of birth ball techniques that support labor so that it can run physiologically. It is also one of the most helpful methods of responding to pain in an active way and reducing the duration of labor in the active phase. This type of research used in this study was a pre-experimental study using a static group comparison research design, with purposive sampling technique where sampling is based on the consideration of the researcher himself. The sample used was 30 inpartum mothers. Analysis of bivariate data using Mann Withney. The results obtained p-value 0.0000 <0.05, which means that there is a significant effect of the implementation of the birth ball technique on the progress of labor. The average progress of labor for a birth ball performed and not performed was different in that the status of the birth ball was carried out 224.3 minutes faster than that for a non-performed birth ball.